Apports de l’évaluation délibérative dans la gestion concertée des ressources communes. L’exemple des marais Tanoé-Ehy - Ettien Brou (VertigO)
The choice of natural resources policies involves stakeholders’ participation with their logical determinants. However, it should not be necessarily that these logical determinants converge on a consensus decision. How to structure the contradictions ? The deliberative approach answers this question with methodological support for debate. Integraal deliberative method has been implemented to formulate a policy in a common pool resource program. The purpose of this report is to present the analysis of the outcomes from this implementation.